NEGOTIATING GENDER ROLES IN CULTURE-BASED CREATIVE ECONOMIES: A STUDY OF THE KAMPOENG LAMA TOURISM VILLAGE COMMUNITY, DELI SERDANG REGENCY - Daniel Ebenezer Silaban (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the influence of gender equality and community participation on affirmative economic development in the tourism village of Hariara Pohan, with tourism village sustainability functioning as a mediating variable. The objective is to understand how social empowerment and cultural governance contribute to equitable and long-term economic benefits in community-based tourism. The research used a quantitative survey method and involved 165 respondents who were actively engaged in tourism and local creative economy activities. A structured questionnaire using a five-point Likert scale was administered, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both direct and indirect causal relationships among the studied variables. The results indicate that gender equality and community participation significantly enhance tourism village sustainability, particularly through strengthened decision-making roles, cultural heritage protection, and collective responsibility. Both variables also directly influence affirmative economic development by improving micro-enterprise growth, access to capital, and fair distribution of tourism income across households. Furthermore, tourism village sustainability mediates these relationships, demonstrating that social empowerment leads to stable economic outcomes when supported by cultural preservation and environmental stewardship. In conclusion, the study underscores that sustainable and inclusive tourism development requires not only economic planning, but also equitable participation, gender-balanced leadership, and strong cultural identity. These elements are essential for building resilient rural tourism economies.